Forms and Methods of Assessing Students' Educational Achievements - As a Factor in Achieving Learning Goals (Journal of Pedagogical Inventions and Practices, 2023)
The article discusses modern forms and methods of assessing students' knowledge and skills. The impact of changes in content on technology, teaching aids, and ways to increase students' responsibility for the learning outcome are considered